Karakteristik Fisik Morfologi, pH, dan Waktu Alir Serbuk Serat Ampas Kelapa sebagai Bahan Pengisi Sediaan Farmasi: Physical Characteristics Morphology, pH, and Flow Time of Coconut Pulp Fiber Powder as a Filling Material for Pharmaceutical Preparations - Amatullah Syarifah; Tuti Sri Suhesti; Rehana (Jurnal Sains dan Kesehatan, 2022)
Utilization of coconut pulp fiber is still low so that it can be used in the pharmaceutical industry. This study aims to determine the physical characteristics of morphology, pH, and flow time of coconut pulp fiber powder as a filler in pharmaceutical preparations. The procedure of this research was started by making coconut pulp fiber powder, morphological characteristic test, pH test, and flow time test. The results of this study are: (1) Morphological characteristics test, coconut pulp fiber powder has a slightly yellowish white color, tasteless, odorless, and roughness of 426-600 m which means it is in accordance with pharmaceutical grade; (2) the pH of the powder is 6.43 which means it is close to neutral; and (3) the flow time test showed a result of 4.73 grams/second, which means the powder can flow well. In conclusion, coconut pulp powder can be used as a filler in pharmaceutical preparations.